Hypoxia-driven intratumor heterogeneity and immune evasion. (1st November 2020) - Terry, Stéphane; Engelsen, Agnete S.T.; Buart, Stéphanie; Elsayed, Walid Shaaban; Venkatesh, Goutham Hassan; Chouaib, Salem
Abstract: While it is widely accepted that high intratumoral heterogeneity confers serious challenges in the emerging resistance and the subsequent effective therapeutic targeting of cancer, the underlying biology of intratumoral heterogeneity remains elusive. In particular, it remains to be fully elucidated how microenvironmental factors shape genetic and non-genetic heterogeneity, which in turn determine the course of tumor evolution and clinical progression. In this context, hypoxia, a hallmark of most growing cancers, characterized by decreased O2 partial pressure is a key player of the tumor microenvironment. Despite extensive data indicating that hypoxia promotes cellular metabolic adaptation, immune suppression and various steps of tumor progression via hypoxia regulated gene transcription, much less is known about the role of hypoxia in mediating therapy resistance as a driver of tumor evolution through genetic and non-genetic mechanisms. In this review, we will discuss recent evidence supporting a prominent role of hypoxia as a driver of tumor heterogeneity and highlight the multifaceted manner by which this in turn could impact cancer evolution, reprogramming and immune escape. Finally, we will discuss how detailed knowledge of the hypoxic footprint may open up new therapeutic avenues for the management of cancer. Highlights: Tumor hypoxia may have major impact on intratumor heterogeneity (ITH). ITH can manifest via genetic and non-genetic variations in cancer cell populations. Both genetic and non-genetic changes can lead to increased tumor plasticity. Hypoxia-driven ITH may generate cancer clones resistant to anti-tumor immunity. Targeting hypoxia or tumor plasticity might be beneficial for cancer treatment.